Intradiscal ozone therapy for lumbar disc herniation - Ozcan, Sibel; Muz, Arzu; Yildiz Altun, Aysun; Onal, Selami Ates (Cellular and Molecular Biology, 2018)
The rationale behind intradiscal O2-O3 therapy is the pain elicited by the mechanical compression of the nerve root, which is associated with periganglionic and periradicular inflammation. This study aimed to determine the effect of intradiscal ozone injection on pain score and satisfaction of patients with low back pain (LBP) secondary to disc herniation. Patients with LBP diagnosed with disc herniation were enrolled in this clinical trial. After prepping and draping the area, intradiscal injection of ozone/oxygen mixture (10 ml, 25Î¼g/ml) was performed under fluoroscopy guide (c-arm). Pain score and patient satisfaction were assessed prior to the injection (baseline) and 1, 3, 6, 12 and 24 months after the injection. Sixty three patients (24 males, 39 females) with mean age of 53.3 ±2.0 y enrolled in the study. The mean±standard deviation (SD) of pain score before intervention was 6.968 ±0.11. Pain score was reduced to 4.25±0.19 at 1 month, 4.33±0.20 at 3 months, 4.87 ±0.21 at 6 months and 5.22 ±0.20 at 24 months. According to the modified MacNab scale success of pain relief was as follows: excellent: 4 (6.3%), good: 17 (26.98 %), sufficient: 13 (20.63 %), poor: 13 (20.63 %), no result: 11 (17.46%), negative: 4 (6.3 %). Intradiscal ozone therapy was determined to provide improved outcomes in patients with single level of bulging and protrusion.